CONSTRUCTION OF BOARDING SCHOOL EDUCATION SYSTEM ACCORDING TO NURCHOLISH MADJID - Anwar, Moh. Sholehuddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Pesantren is an Islamic educational institution that has its own education system in Indonesia, especially on the island of Java. In the eyes of the people fundamentalists, pesantren are often associated with traditional aspects; oldfashioned and conservative. That view, also associated with the conditions of the times that continue to grow, and the needs of people who are increasingly diverse in the world education. So that Nurcholis Madjid, in several of his books, also reviews it what is the condition of traditional pesantren, and reforming the education system. This is done so that traditional pesantren are not considered old-fashioned, conservative and outdated. Departing from the contribution of thought, the author does library research research with a descriptive hermeneutic approach to Nurcholish Madjid's works related to research themes